Social Net Intervention as Social Support Model - Gvaldaitė, Lijana (Acta Paedagogica Vilnensia, 2004)
„Network" - this is the notion widely used in the modern society, and in the scientific language this term is used in various spheres starting from economics till electronics. „Network" appeared and in the sphere of social science as well: during the last decades it has become the object of research in anthropology, ethnology, sociology, social psychology, psychoanalysis and others. The method of Canadian scientists C. Brodeur and R. Rousseau is analysed in the article as one of the social support forms. In Europe this method was spread due to the specialists of Social work department headed by professor L. Sanicola from Parma university in ltaly. The peculiarities of this method and its innovation in the context of social support are presented as well as its functional aspects, opportunities of practical network intervention application are indicated, the stages of intervention are analysed, presenting the analyses of concrete case, the role of the social worker is revealed as well as philosophy of these actions.
Keywords: social net; social support; intervention; support model